1989
DOI: 10.1136/bmj.298.6677.875
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac catheterisation by the Judkins technique as an outpatient procedure.

Abstract: Objective-To assess the safety and cost benefit of left heart catheterisation by a modified Judkins technique performed as a day patient procedure.Design-Review study ofcase notes ofconsecutive patients examined by the procedure over three years January 1984 to December 1986).Setting-Outpatient referrals in a regional cardiac centre within a district general hospital.Patients-Nine hundred patients aged 18-76 (mean 54) selected at a previous clinic as suitable for the procedure.Main results-Eight hundred and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…We report a complication rate higher than that in the CECCC report2(1.9% with 95% confidence interval (CI) 1.3 to 2.5, v 0.8% with 95% CI 0.7 to 0.9), but similar to recent data from another UK centre9 (4.4% with 95% CI 3.1 to 5.8). The increased rate of vascular complications in the non-femoral group may be correlated with the high proportion of patients with severe peripheral vascular disease in that group (∼50%).…”
Section: Discussionsupporting
confidence: 87%
“…We report a complication rate higher than that in the CECCC report2(1.9% with 95% confidence interval (CI) 1.3 to 2.5, v 0.8% with 95% CI 0.7 to 0.9), but similar to recent data from another UK centre9 (4.4% with 95% CI 3.1 to 5.8). The increased rate of vascular complications in the non-femoral group may be correlated with the high proportion of patients with severe peripheral vascular disease in that group (∼50%).…”
Section: Discussionsupporting
confidence: 87%
“…Numerous studies have demonstrated that outpatient coronary angiography may be performed safely and with low complication rates [2,5,8,11,13,17,18,20,22,23,25,28]. The safety of outpatient cardiac catheterization and coronary angiography is, however, dependent upon a variety of factors.…”
Section: Safetymentioning
confidence: 98%
“…The pressure to investigate more patients with ischaemic heart disease by coronary angiography has led to a move to study many of these patients as day cases [1,2]. The use of small diameter (5F), coronary catheters has been promoted [3] with the suggestion that they may have advantages related to smaller puncture sites and that they are more suitable for outpatient angiography.…”
Section: Introductionmentioning
confidence: 99%